Pemetaan Keterampilan Metakognitif dalam Pembelajaran Sains: Fungsi dan Tren Penelitian 2014-2023 - Hidayati, Sri (Inovasi: Jurnal Diklat Keagamaan, 2024)
The development of metacognitive skills for learning has emerged as a major topic in educational research. This study aimed to: (1) map the function of metacognitive skills; and (2) identify study trends in metacognitive skills over the last ten years in science learning. Systematic Review of Literature (SLR) was used as the study methodology. Data were extracted from scientific publications published in leading international journals using the Scopus index and then uploaded to the Google Scholar and Scopus databases. The title and keywords "Metacognitive Skills" and "Metacognitive Skills in Science Learning" were used in the article search, which was limited to the last ten years, starting in 2014 and ending in 2023. The results showed that there were 18426 articles in the database sources and 40 remaining for review after selection. Study findings regarding the function of metacognitive skills showed that 65% of these skills functioned as output, while 35% functioned as input. Furthermore, it was found that most study on metacognitive skills in science learning was conducted at the university level (50%) and high school level (25%). In terms of scientific disciplines, biology accounted for 44% of all disciplines. Emotional regulation was a dominant aspect of metacognitive skill learning and development.